2011
DOI: 10.1007/s10545-011-9404-7
|View full text |Cite
|
Sign up to set email alerts
|

Facial‐muscle weakness, speech disorders and dysphagia are common in patients with classic infantile Pompe disease treated with enzyme therapy

Abstract: Classic infantile Pompe disease is an inherited generalized glycogen storage disorder caused by deficiency of lysosomal acid α-glucosidase. If left untreated, patients die before one year of age. Although enzyme-replacement therapy (ERT) has significantly prolonged lifespan, it has also revealed new aspects of the disease. For up to 11 years, we investigated the frequency and consequences of facial-muscle weakness, speech disorders and dysphagia in long-term survivors. Sequential photographs were used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…Although ERT has become the standard of care for Pompe disease, the clinical benefits of ERT have been confounded by immune responses (Kishnani et al, 2007) and progression of neuromuscular impairments (Nicolino et al, 2009;Chakrapani et al, 2010;van Gelder et al, 2012). In particular, longer-term evaluations reveal progressive respiratory insufficiency and a requirement for invasive ventilation in many surviving subjects, despite the chronic use of ERT (Nicolino et al, 2009;Chakrapani et al, 2010).…”
mentioning
confidence: 99%
“…Although ERT has become the standard of care for Pompe disease, the clinical benefits of ERT have been confounded by immune responses (Kishnani et al, 2007) and progression of neuromuscular impairments (Nicolino et al, 2009;Chakrapani et al, 2010;van Gelder et al, 2012). In particular, longer-term evaluations reveal progressive respiratory insufficiency and a requirement for invasive ventilation in many surviving subjects, despite the chronic use of ERT (Nicolino et al, 2009;Chakrapani et al, 2010).…”
mentioning
confidence: 99%
“…Retrospective reviews have shown improvement in cardiac and lung function and gross motor function in long-term survivors . Persistent deficiencies in hearing loss, risk of arrhythmias, dysphagia, osteopenia, fecal incontinence, and other longterm complications have been addressed (Jones et al 2010;van Gelder et al 2012;Tan et al 2013). However, we are unaware of any published data on LUTS and urinary incontinence in children with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence is an often undertreated condition that can greatly affect quality of life (Jones et al 2010;van Gelder et al 2012;Tan et al 2013;Thibodeau et al 2013). Ninety percent of children achieve daytime urinary continence by the age of 5 (Hunskaar et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…9 So, early and regular swallowing assessment and development of a safe feeding plan are recommended to prevent aspiration and pneumonia that represent high-risk complications for all patients. 10 The point of view of the cardiologist From a cardiologist's point of view, Pompe disease is one of the most important (and devastating) cause of hypertrophic cardiomyopathy in newborns and neonates (infantile classic form). 11 In 1932, a Dutch pathologist, Dr. Johannes Pompe, described the case of a 7month old infant who died suddenly for a severe idiopathic hypertrophy of the heart.…”
Section: Classic Infantile Diseasementioning
confidence: 99%